A heat treatment method for strengthening the high temperature compression creep properties of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution and configuration of the second phase
By regulating the existence and distribution of alloying elements and the second phase, a heat treatment method that induces carbide precipitation and regulates the second phase distribution configuration is used to solve the problem of insufficient creep performance of high niobium TiAl alloys, and its high-temperature compression creep performance is significantly improved.
Patent Information
- Application Number
- CN202411253848.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The creep performance of high niobium TiAl alloy is insufficient, which limits its application in high-temperature and high-stress environments such as aircraft engine blades.
By regulating the presence, morphology, size and distribution of the alloying elements and the second phase in the tissue, a heat treatment method that induces carbide precipitation and regulates the second phase distribution configuration is used to improve the high-temperature compression creep performance of high-niobium TiAl alloy. Specific steps include preheating treatment, homogenizing annealing treatment, solid solution treatment and aging treatment.
While keeping the original structure of the alloy basically unchanged and the room temperature plasticity does not significantly reduce, the high-temperature creep performance of high niobium TiAl alloy is significantly improved and the performance of the material under compression load is improved.
Smart Images

Figure CN119101821B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high niobium TiAl alloys, and in particular to a heat treatment process for improving the high temperature creep properties of high niobium TiAl alloys by regulating the existence form, morphology, size and distribution of alloying elements and second phases in the organization. Background Art
[0002] Aircraft engines are known as the "crown jewel of industry", and turbine blades are their core parts, so strict requirements are placed on the operating temperature and high-temperature performance of engine blade materials. Currently, most aircraft engine blade materials are nickel-based high-temperature alloys. However, the high density of nickel-based high-temperature alloys significantly reduces the flexibility of aircraft and increases energy loss. Studies have found that the density of high-niobium TiAl alloys is only half of that of nickel-based high-temperature alloys, and it has many advantages such as high specific strength and good oxidation resistance. Therefore, using high-niobium TiAl alloys to replace nickel-based high-temperature alloys in engine blades has become a feasible means.
[0003] In the actual service environment, the blade will be subjected to high temperature and stress, which will cause creep deformation, thus affecting the microstructure and performance of the alloy. However, the insufficient creep performance of high niobium TiAl alloy will limit its actual service life. Therefore, it is necessary to develop high niobium TiAl alloy with excellent creep performance. The typical microstructures of high niobium TiAl alloys are divided into four categories: near-γ microstructure, bimodal microstructure, near-lamellar microstructure and full-lamellar microstructure. Among them, the alloy with full-lamellar microstructure has the best creep resistance, followed by near-lamellar microstructure, while the alloy with near-γ microstructure and bimodal microstructure has poor creep performance. Therefore, most current studies are to improve the creep performance of the alloy by regulating the full-lamellar microstructure through reasonable processes, but the defect of poor room temperature plasticity of the full-lamellar microstructure limits the application of TiAl alloys to a certain extent. Therefore, it is necessary to seek a process that does not significantly reduce the room temperature plasticity of the alloy while improving the creep performance of the alloy. From a large number of literature searches, it is known that one of the main means to improve the high-temperature creep properties of high-niobium TiAl alloys is alloying, that is, adding alloying substances such as W, Cr, C, N, Y, B and Si to high-niobium TiAl alloys. These alloying substances can play a role in fine grain strengthening, solid solution strengthening or second phase strengthening. However, current research focuses on exploring the effects of adding different types of alloying substances on alloy properties, and there is less research on the regulation of the properties of the alloying substances themselves. Therefore, this patent has developed a heat treatment process to improve the creep properties of high-niobium TiAl alloys by regulating the reinforcing phase without changing the original structure. In addition, the current creep behavior of TiAl alloys is mostly carried out under tensile stress, but in actual service environments, blades are subjected to a variety of loads, such as compressive stress, so it is also necessary to study the compressive creep behavior of TiAl alloys at high temperatures. Summary of the invention
[0004] In order to solve the technical problem of insufficient creep performance of high niobium TiAl alloy, the present invention provides a heat treatment method for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution configuration of the second phase.
[0005] The present invention provides a heat treatment process for improving the high temperature creep performance of high niobium TiAl alloy by regulating the existence form, morphology, size and distribution of alloying elements and second phases in the organization. First, a high niobium TiAl alloy strengthened by C and Y2O3 with a near-lamellar structure is prepared; then, under the premise of keeping the original organization morphology of the alloy basically unchanged and the room temperature plasticity not significantly reduced, in order to regulate the ideal alloying material properties, appropriate heat treatment parameters are selected to perform a two-step heat treatment of solid solution and aging on the alloy; by performing high temperature compression creep tests on the alloy before and after the heat treatment, it is confirmed that a high niobium TiAl alloy with good creep performance is obtained.
[0006] A heat treatment method for strengthening the high temperature compression creep performance of a high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration is specifically carried out in the following steps:
[0007] 1. Raw materials are obtained according to the atomic percentage: Al is 40% to 46%, Nb is 5% to 8%, Mo is 0.5% to 1.5%, Cr is 0.5% to 1.5%, C is 0.3% to 1.0%, Y2O3 is 0.05% to 0.1% and the balance is Ti. The raw materials include sponge Ti particles, high-purity Ti rods, pure Al blocks, pure Cr particles, Al-Nb master alloy particles, Al-Mo master alloy particles, Y2O3 powder and C powder;
[0008] 2. ① Preheating treatment: put the raw materials weighed in step 1 into an oven and preheat them at a temperature of 100-200°C for 30-60 minutes; ② Place the raw materials in a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace, spread the sponge Ti particles at the bottom of the copper crucible, and place the high-purity Ti rod upright around the inner wall of the copper crucible. Use Al foil to wrap the C powder and add it to the copper crucible, then put pure Cr particles, Al-Nb intermediate alloy particles and Al-Mo intermediate alloy particles, and then put the pure Al block on top, and use Al foil to wrap the Y2O3 powder and put it in the secondary feeding hopper; ③ Vacuum treatment: remove the air in the equipment, and then fill the furnace with protective gas until the pressure in the furnace is 800Pa; ④ Heat and melt, the initial heating power is 15-40 kW, after the pure Al block is melted, increase the power to 45-60kW, after the high-purity Ti rod is melted, continue to increase the power to 65-80kW, after all the raw materials are completely melted, perform electromagnetic stirring, reduce the power to 15-30kW, control the secondary feeding hopper to add Y2O3 powder wrapped in Al foil; continue to increase the power to 70-90kW, keep it for 10-15min, and perform electromagnetic stirring; ⑤ reduce the power and let the melt stand, after the alloy melt solidifies, increase the power to 70-90kW again, keep it for 10-15min, and perform electromagnetic stirring at the same time; ⑥ repeat step ⑤ 3-5 times; ⑦ inject the alloy melt into the mold to solidify, cool it to room temperature, take it out, and obtain a high niobium TiAl alloy ingot;
[0009] 3. Homogenization annealing treatment: the high niobium TiAl alloy ingot obtained in step 2 is kept at 940-960° C. for 30-50 hours, and then cooled to room temperature to obtain a cast high niobium TiAl alloy;
[0010] 4. Use differential scanning calorimetry to perform differential thermal analysis and measure the α phase transformation temperature T of the as-cast high niobium TiAl alloy in step 3. α , γ phase transition temperature T e ;
[0011] 5. Solution treatment: The as-cast high niobium TiAl alloy obtained in step 3 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised uniformly at a rate of 10-20°C / min to 580-620°C, and maintained for 2-8 minutes; then the temperature is raised uniformly at a rate of 7-15°C / min to the target temperature (T α -30℃)~(T α -10℃), keep for 0.5~1.5h; then cool to room temperature with the furnace;
[0012] 6. Aging treatment: Place the as-cast high niobium TiAl alloy after the solid solution treatment in step 5 into a heat treatment furnace and perform step-by-step heating: uniformly heat to 580-620°C at a rate of 10-20°C / min, and maintain for 2-8 minutes; then uniformly heat to 900-1000°C at a rate of 7-15°C / min, and maintain for 10-15 hours; then cool to room temperature with the furnace to complete.
[0013] The present invention reasonably controls the matrix composition of a high-niobium TiAl alloy, then adds appropriate amounts of C and Y2O3 into the alloy to improve its room temperature performance and creep performance, and finally obtains an alloy with a near-lamellar structure (better creep performance and room temperature plasticity); then, through a limited heat treatment process (solid solution in the (α+γ) two-phase region temperature range for a period of time and furnace cooling, then aging treatment at low temperature for a long time and furnace cooling), under the premise that the original structure morphology of the alloy remains basically unchanged (still a near-lamellar structure) and the room temperature plasticity of the alloy is not significantly reduced, the ideal existence form, morphology, size and distribution of C and Y2O3 in the structure are regulated to further enhance the creep performance of the alloy.
[0014] Beneficial effects of the present invention:
[0015] The original structure of the high niobium TiAl alloy prepared by the present invention is a near-lamellar structure, without carbide precipitation, and with the presence of a large-sized strip-shaped Y2O3 second phase; after heat treatment, the structure morphology remains basically unchanged, still a near-lamellar structure, but carbides are precipitated at the lamellar interface, Y2O3 becomes a small ellipsoid, and part of the B2 phase also shows spheroidization. The improvement in high-temperature creep performance is mainly due to the precipitation of carbides at the lamellar interface after heat treatment and the spheroidization behavior of the B2 phase and Y2O3. This two-step heat treatment process can simplify the production process, and by regulating the existence form, morphology, size and distribution of alloying elements and second phases in the organization, the creep performance is significantly improved under the premise that the original organization remains basically unchanged and the room temperature plasticity of the alloy is not significantly reduced, providing a reference for the development and application of high-performance TiAl alloys.
[0016] (1) The present invention successfully prepared a high-niobium TiAl alloy with uniform composition and near-lamellar structure by using a repeated smelting process and introducing multiple electromagnetic stirring. Due to the complex load effects of the alloy during service and the fact that the effect of heat treatment on the compressive creep performance is not significant in most current studies, the focus is on improving the creep performance of the material under compressive load.
[0017] (2) In order to adjust the properties of the ideal alloying materials (C and Y2O3), the present invention has developed a two-step heat treatment process of solid solution and aging treatment. This process can ensure the uniformity of the alloy composition and structure, and promote the precipitation of carbides dissolved in the matrix and the spheroidization behavior of B2 phase and Y2O3. This heat treatment process is relatively simple, can shorten the test cycle, and is suitable for the performance control of complex structural parts. Moreover, both steps of heat treatment adopt the furnace cooling method to avoid cracking and damage to the alloy. In addition, the organizational morphology remains basically unchanged after heat treatment, and is still a near-lamellar structure, which avoids the reduction of the room temperature plasticity of the alloy.
[0018] (3) The heat treatment process proposed in the present invention significantly improves the high-temperature creep performance of the alloy by reasonably regulating the existence form, morphology, size and distribution of C and Y2O3 in the structure, while keeping the original structure of the alloy basically unchanged and the room temperature plasticity of the alloy not significantly reduced. The mechanism of performance improvement is as follows: the carbides precipitated at the interface of the lamellar layer can pin the lamellar interface and stabilize the lamellar structure; the hindering effect of the relative dislocation of the spherical B2; the dispersion strengthening and second phase strengthening effect of the tiny ellipsoidal Y2O3. In addition, Y2O3 plays a certain role in promoting the precipitation of carbides, and the synergistic effect of Y2O3 and carbides significantly improves the creep performance of the alloy.
[0019] The method of the invention is used for improving the creep performance of high-niobium TiAl alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The microstructure photos of the as-cast high-niobium TiAl alloy obtained in step 3 of Example 1, wherein (a) is a B2 phase morphology image; (b) is a Y2O3 morphology image; (c) is a complete layer image;
[0021] Figure 2 The microstructure photos of the as-cast high niobium TiAl alloy after solution and aging treatment in Example 1, wherein (a) is a B2 phase morphology; (b) is a Y2O3 morphology; (c) is a carbide precipitation diagram in the lamellar part;
[0022] Figure 3 This is a compressive creep strain-time curve of the as-cast high niobium TiAl alloy before and after heat treatment in Example 1. DETAILED DESCRIPTION
[0023] Specific implementation method 1: This implementation method is a heat treatment method for strengthening the high-temperature compression creep performance of high-niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, which is specifically carried out in the following steps:
[0024] 1. Raw materials are obtained according to the atomic percentage: Al is 40% to 46%, Nb is 5% to 8%, Mo is 0.5% to 1.5%, Cr is 0.5% to 1.5%, C is 0.3% to 1.0%, Y2O3 is 0.05% to 0.1% and the balance is Ti. The raw materials include sponge Ti particles, high-purity Ti rods, pure Al blocks, pure Cr particles, Al-Nb master alloy particles, Al-Mo master alloy particles, Y2O3 powder and C powder;
[0025] 2. ① Preheating treatment: put the raw materials weighed in step 1 into an oven and preheat them at a temperature of 100-200°C for 30-60 minutes; ② Place the raw materials in a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace, spread the sponge Ti particles at the bottom of the copper crucible, and place the high-purity Ti rod upright around the inner wall of the copper crucible. Use Al foil to wrap the C powder and add it to the copper crucible, then put pure Cr particles, Al-Nb intermediate alloy particles and Al-Mo intermediate alloy particles, and then put the pure Al block on top, and use Al foil to wrap the Y2O3 powder and put it in the secondary feeding hopper; ③ Vacuum treatment: remove the air in the equipment, and then fill the furnace with protective gas until the pressure in the furnace is 800Pa; ④ Heat and melt, the initial heating power is 15-40 kW, after the pure Al block is melted, increase the power to 45-60kW, after the high-purity Ti rod is melted, continue to increase the power to 65-80kW, after all the raw materials are completely melted, perform electromagnetic stirring, reduce the power to 15-30kW, control the secondary feeding hopper to add Y2O3 powder wrapped in Al foil; continue to increase the power to 70-90kW, keep it for 10-15min, and perform electromagnetic stirring; ⑤ reduce the power and let the melt stand, after the alloy melt solidifies, increase the power to 70-90kW again, keep it for 10-15min, and perform electromagnetic stirring at the same time; ⑥ repeat step ⑤ 3-5 times; ⑦ inject the alloy melt into the mold to solidify, cool it to room temperature, take it out, and obtain a high niobium TiAl alloy ingot;
[0026] 3. Homogenization annealing treatment: the high niobium TiAl alloy ingot obtained in step 2 is kept at 940-960° C. for 30-50 hours, and then cooled to room temperature to obtain a cast high niobium TiAl alloy;
[0027] 4. Use differential scanning calorimetry to perform differential thermal analysis and measure the α phase transformation temperature T of the as-cast high niobium TiAl alloy in step 3. α , γ phase transition temperature T e ;
[0028] 5. Solution treatment: The as-cast high niobium TiAl alloy obtained in step 3 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised uniformly at a rate of 10-20°C / min to 580-620°C, and maintained for 2-8 minutes; then the temperature is raised uniformly at a rate of 7-15°C / min to the target temperature (T α -30℃)~(T α -10℃), keep for 0.5~1.5h; then cool to room temperature with the furnace;
[0029] 6. Aging treatment: Place the as-cast high niobium TiAl alloy after the solid solution treatment in step 5 into a heat treatment furnace and perform step-by-step heating: uniformly heat to 580-620°C at a rate of 10-20°C / min, and maintain for 2-8 minutes; then uniformly heat to 900-1000°C at a rate of 7-15°C / min, and maintain for 10-15 hours; then cool to room temperature with the furnace to complete.
[0030] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the mass purity of the sponge Ti particles in step 1 is >99.9%, the mass purity of the high-purity Ti rod is >99.9%, the mass purity of the pure Al block is >99.9%, and the mass purity of the pure Cr particles is >99.9%. Others are the same as specific embodiment 1.
[0031] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: in step 1, the Nb content in the Al-Nb master alloy particles is 52.4wt.%, and the Mo content in the Al-Mo master alloy particles is 50.5wt.%. The rest is the same as specific embodiment 1 or 2.
[0032] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: step 2 is a vacuum treatment to remove air from the equipment until the vacuum degree reaches below 5 Pa. The rest is the same as specific embodiments 1 to 3.
[0033] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that the protective gas in step 2 is argon gas. The rest is the same as specific implementation modes 1 to 4.
[0034] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that step 3 adopts a furnace cooling method. The rest is the same as specific implementation methods 1 to 5.
[0035] Specific implementation method 7: This implementation method is different from the specific implementation methods 1 to 6 in that: Step 4 measures T α The temperature is 1360-1370° C. The rest is the same as that of the first to sixth embodiments.
[0036] Specific implementation eight: This implementation differs from specific implementations one to seven in that: Step four measures T e The temperature is 1220-1230° C. The rest is the same as that of the first to seventh embodiments.
[0037] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the matrix structure of the as-cast high niobium TiAl alloy after the solid solution treatment in step 5 is a near-lamellar structure, no carbide precipitation, C exists in the form of solid solution, and Y2O3 exists in the form of large-sized strips. Other aspects are the same as specific embodiments 1 to 8.
[0038] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in the as-cast high-niobium TiAl alloy after aging treatment in step 6, C is precipitated in the form of fine short rods or granular carbides, and Y2O3 exists in the form of micron-sized particles or spheres. Other aspects are the same as specific embodiments 1 to 9.
[0039] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.
[0040] Embodiment 1:
[0041] A heat treatment method for strengthening the high temperature compression creep performance of a high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration is specifically carried out in the following steps:
[0042] 1. Raw materials are obtained according to the atomic percentage: Al is 43%, Nb is 6%, Mo is 1.0%, Cr is 1.0%, C is 0.5%, Y2O3 is 0.05% and the balance is Ti, the raw materials include sponge Ti particles, high-purity Ti rods, pure Al blocks, pure Cr particles, Al-Nb master alloy particles, Al-Mo master alloy particles, Y2O3 powder and C powder; the mass purity of the sponge Ti particles is greater than 99.9%, the mass purity of the high-purity Ti rods is greater than 99.9%, the mass purity of the pure Al blocks is greater than 99.9%, the mass purity of the pure Cr particles is greater than 99.9%, the Nb content in the Al-Nb master alloy particles is 52.4wt.%, and the Mo content in the Al-Mo master alloy particles is 50.5wt.%;
[0043] 2. ① Preheating treatment: put the raw materials weighed in step 1 into an oven and preheat them at a temperature of 100-200°C for 30-60 minutes; ② Place the raw materials in a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace, spread the sponge Ti particles at the bottom of the copper crucible, and place the high-purity Ti rod upright around the inner wall of the copper crucible. Use Al foil to wrap the C powder and add it to the copper crucible, then put pure Cr particles, Al-Nb intermediate alloy particles and Al-Mo intermediate alloy particles, and then put the pure Al block on top, and use Al foil to wrap the Y2O3 powder and put it in the secondary feeding hopper; ③ Vacuum treatment: remove the air in the equipment until the vacuum degree reaches below 5Pa, and then fill the furnace with argon until the pressure in the furnace is 800Pa; ④ Heating and smelting, the initial heating power ⑤ The power is increased to 15-40kW. After the pure Al block is melted, the power is increased to 45-60kW. After the high-purity Ti rod is melted, the power is further increased to 65-80kW. After all the raw materials are completely melted, electromagnetic stirring is performed, and the power is reduced to 15-30kW. The secondary feeding hopper is controlled to add Y2O3 powder wrapped in Al foil; the power is further increased to 70-90kW, maintained for 10-15 minutes, and electromagnetic stirring is performed; ⑤ The power is reduced and the melt is allowed to stand for treatment. After the alloy melt solidifies, the power is increased to 70-90kW again, maintained for 10-15 minutes, and electromagnetic stirring is performed at the same time; ⑥ Step ⑤ is repeated 3-5 times; ⑦ The alloy melt is injected into the mold for solidification, and after cooling to room temperature, it is taken out to obtain a high niobium TiAl alloy ingot;
[0044] 3. Homogenization annealing treatment: the high niobium TiAl alloy ingot obtained in step 2 is kept at 950°C for 36 hours, and then cooled to room temperature with the furnace to obtain a cast high niobium TiAl alloy (cast Ti-43Al-6Nb-1Mo-1Cr-0.5C-0.05Y2O3 alloy);
[0045] 4. Use differential scanning calorimetry to perform differential thermal analysis and measure the α phase transformation temperature T of the as-cast high niobium TiAl alloy in step 3. α At 1360-1370°C, the γ phase transition temperature T e At 1220-1230℃;
[0046] 5. Solution treatment: Place the as-cast high-niobium TiAl alloy obtained in step 3 into a heat treatment furnace, and then perform step-by-step heating: uniformly heat to 580-620°C at a rate of 10-20°C / min, and maintain for 2-8 minutes; then uniformly heat to the target temperature of 1340°C at a rate of 7-15°C / min, and maintain for 1 hour; and then cool to room temperature with the furnace;
[0047] 6. Aging treatment: Place the as-cast high niobium TiAl alloy after the solid solution treatment in step 5 into a heat treatment furnace and perform step-by-step heating: uniformly heat to 580-620°C at a rate of 10-20°C / min, and maintain for 2-8 minutes; then uniformly heat to 950°C at a rate of 7-15°C / min, and maintain for 12 hours; then cool to room temperature with the furnace to complete.
[0048] Figure 1 The microstructure photos of the cast high niobium TiAl alloy obtained in step 3 of Example 1, wherein (a) is a B2 phase morphology image; (b) is a Y2O3 morphology image; (c) is a complete lamellar image; it can be determined from the figure that the structure of the alloy is a near lamellar structure, Figure 1 (a) It was found that the B2 phase in the as-cast structure was mostly in the form of long strips. Figure 1 In (b), it can be clearly seen that there is a bright white, long, and larger Y2O3 second phase in the structure. Figure 1 (c) The lamellar structure of the as-cast alloy was found to be complete and smooth.
[0049] Figure 2 The microstructure of the as-cast high-niobium TiAl alloy after solution and aging treatment in Example 1 is shown in Figure 1, where (a) is the B2 phase morphology; (b) is the Y2O3 morphology; (c) is the carbide precipitation diagram in the lamellar part; it can be seen from the figure that the structure of the alloy is still close to the lamellar structure, and the structure morphology before and after the heat treatment is basically unchanged. Figure 2 (a) It can be found that part of the B2 phase has spheroidized after heat treatment. Figure 2 As can be seen in (b), compared with the cast alloy, most of the Y2O3 in the microstructure after heat treatment has changed from long strips to spheres, and its size has been significantly reduced and dispersed in the microstructure. In addition, most of the Y2O3 appears near the grain boundary, indicating that during heat treatment, Y2O3 can act as a heterogeneous nucleation point to promote the nucleation of grains. The nucleation and growth of grains promote the precipitation of carbides to a certain extent. Figure 2 (c) It can be seen that the lamellar structure of the alloy microstructure after heat treatment is relatively disordered, and carbide precipitation occurs in the lamellar area.
[0050] The high-niobium TiAl alloy after heat treatment (aging and solution treatment) in Example 1 and the high-niobium TiAl alloy obtained without heat treatment in step 3 were subjected to high-temperature compression creep test:
[0051] (1) Preliminary preparation: Cylinders with a size of 6 mm × 9 mm were cut from the as-cast high-niobium TiAl alloy before and after heat treatment as cylindrical samples;
[0052] (2) Creep test: ① Place the cylindrical sample in the center between the upper and lower pressure heads of the RDL-50 electronic creep endurance tester; ② Apply a low preload (100-250N) to fix the sample; ③ Fix three thermocouples on the upper pressure head, the lower pressure head and the vicinity of the cylindrical sample to monitor the temperature in real time; ④ Close the heating furnace and start heating at a rate of 10-20℃ / min. When the set creep temperature of 850℃ is reached, keep it warm for 30-55min to ensure that the temperature of all parts of the sample is uniform; ⑤ After the insulation is completed, load at a rate of 100-150N / s until the creep stress reaches 250MPa, and keep the load at a constant stress for 50h; ⑥ After the creep test is completed, remove the load within 5-10s, and then let the sample cool with the furnace; ⑦ After cooling to room temperature, take out the sample after the creep test, and draw a creep curve based on the creep data to analyze the effect of heat treatment on the high-temperature compression creep properties of the alloy.
[0053] Figure 3 The following is a compression creep strain-time curve of the as-cast high niobium TiAl alloy before and after heat treatment in Example 1. It can be seen from the figure that the strain of the as-cast alloy after 50h creep is 11.76%, and the strain of the alloy after 50h creep is only 4.74%. The creep strain of the alloy after heat treatment is significantly reduced, indicating that the compression creep performance of the alloy is significantly improved.
[0054] From the above tests, it can be seen that, under the premise that the original structure of the alloy remains basically unchanged and the room temperature plasticity is not significantly reduced, in order to regulate the existence form, morphology, size and distribution of reasonable alloying substances in the structure, the present invention has successfully developed a two-step heat treatment process of solid solution and aging. This process significantly improves the high temperature creep performance of high niobium TiAl alloy by promoting the precipitation of carbides and the spheroidization behavior of B2 phase and Y2O3.
Claims
1. A heat treatment method for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution and configuration of the second phase, characterized in that The method is specifically carried out in the following steps:
1. Raw materials are obtained according to the atomic percentage: Al is 40% to 46%, Nb is 5% to 8%, Mo is 0.5% to 1.5%, Cr is 0.5% to 1.5%, C is 0.3% to 1.0%, Y2O3 is 0.05% to 0.1% and the balance is Ti. The raw materials include sponge Ti particles, high-purity Ti rods, pure Al blocks, pure Cr particles, Al-Nb master alloy particles, Al-Mo master alloy particles, Y2O3 powder and C powder; 2. ① Preheating treatment: put the raw materials weighed in step 1 into an oven and preheat them at a temperature of 100-200°C for 30-60 minutes; ② Place the raw materials in a copper crucible in a water-cooled copper crucible vacuum induction shell melting furnace, spread the sponge Ti particles at the bottom of the copper crucible, and place the high-purity Ti rod upright around the inner wall of the copper crucible. Use Al foil to wrap the C powder and add it to the copper crucible, then put pure Cr particles, Al-Nb intermediate alloy particles and Al-Mo intermediate alloy particles, and then put the pure Al block on top, and use Al foil to wrap the Y2O3 powder and put it in the secondary feeding hopper; ③ Vacuum treatment: remove the air in the equipment, and then fill the furnace with protective gas until the pressure in the furnace is 800Pa; ④ Heat and melt, the initial heating power is 15-40 kW, after the pure Al block is melted, increase the power to 45-60kW, after the high-purity Ti rod is melted, continue to increase the power to 65-80kW, after all the raw materials are completely melted, perform electromagnetic stirring, reduce the power to 15-30kW, control the secondary feeding hopper to add Y2O3 powder wrapped in Al foil; continue to increase the power to 70-90kW, keep it for 10-15min, and perform electromagnetic stirring; ⑤ reduce the power and let the melt stand, after the alloy melt solidifies, increase the power to 70-90kW again, keep it for 10-15min, and perform electromagnetic stirring at the same time; ⑥ repeat step ⑤ 3-5 times; ⑦ inject the alloy melt into the mold to solidify, cool it to room temperature, take it out, and obtain a high niobium TiAl alloy ingot; 3. Homogenization annealing treatment: the high niobium TiAl alloy ingot obtained in step 2 is kept at 940-960° C. for 30-50 hours, and then cooled to room temperature to obtain a cast high niobium TiAl alloy; 4. Use differential scanning calorimetry to perform differential thermal analysis and measure the α phase transformation temperature T of the as-cast high niobium TiAl alloy in step 3. α , γ phase transition temperature T e ; 5. Solution treatment: The as-cast high niobium TiAl alloy obtained in step 3 is placed in a heat treatment furnace, and then the temperature is raised in a stepwise manner: the temperature is raised uniformly at a rate of 10-20°C / min to 580-620°C, and maintained for 2-8 minutes; then the temperature is raised uniformly at a rate of 7-15°C / min to the target temperature (T α -30℃)~(T α -10℃), keep for 0.5~1.5h; then cool to room temperature with the furnace; 6. Aging treatment: Place the as-cast high niobium TiAl alloy after the solid solution treatment in step 5 into a heat treatment furnace and perform step-by-step heating: uniformly heat to 580-620°C at a rate of 10-20°C / min, and maintain for 2-8 minutes; then uniformly heat to 900-1000°C at a rate of 7-15°C / min, and maintain for 10-15 hours; then cool to room temperature with the furnace to complete.
2. A heat treatment method according to claim 1 to strengthen the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that The mass purity of the sponge Ti particles in step 1 is >99.9%, the mass purity of the high-purity Ti rods is >99.9%, the mass purity of the pure Al blocks is >99.9%, and the mass purity of the pure Cr particles is >99.9%.
3. The heat treatment method according to claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that In step 1, the Nb content in the Al-Nb master alloy particles is 52.4wt.%, and the Mo content in the Al-Mo master alloy particles is 50.5wt.%.
4. The heat treatment method according to claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution and configuration of the second phase, characterized in that Step 2: Vacuum the equipment to remove air until the vacuum degree reaches below 5 Pa.
5. The heat treatment method of claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that The protective gas in step 2 is argon.
6. The heat treatment method of claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that Step three adopts furnace cooling method.
7. The heat treatment method according to claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution and configuration of the second phase, characterized in that Step 4: Measure T α At 1360~1370℃.
8. The heat treatment method according to claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the distribution and configuration of the second phase, characterized in that Step 4: Measure T e At 1220~1230℃.
9. The heat treatment method according to claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that Step 5: After the solid solution treatment, the matrix structure of the as-cast high niobium TiAl alloy is a near-lamellar structure, with no carbide precipitation, C exists in the form of solid solution, and Y2O3 exists in the form of large-sized strips.
10. The heat treatment method of claim 1 for strengthening the high temperature compression creep performance of high niobium TiAl alloy by inducing carbide precipitation and regulating the second phase distribution configuration, characterized in that Step 6: In the as-cast high-niobium TiAl alloy after aging treatment, C precipitates in the form of fine short rods or granular carbides, and Y2O3 exists in the form of micron-sized particles or spheres.
Citation Information
Patent Citations
Cast-condition high-niobium TiAl alloy and method for improving alloy structure of alloy
CN103834843A
High Nb-TiAl alloy added with nano yttrium oxide and preparation method of high Nb-TiAl alloy
CN110819873A